Factual Study of Academic Supervision at Primary and Secondary Educational Levels in Indonesia - Bradley Setiyadi; Muhammad Agrian Nugrah Pratama; Rizal Zamaludin; Aan Komariah; Mohammad Faisal. A Ghani (Jurnal Iqra' : Kajian Ilmu Pendidikan, 2025)
This paper aims to review, identify and synthesize existing research on academic supervision programs at primary and secondary education levels in Indonesia between 2021 and 2024. A total of ten scientific articles covering the topic of academic supervision in Indonesia were collected and analyzed. The review revealed that academic supervision programs implemented in Indonesia aim to improve teacher performance and plan and provide follow-up to the results of the supervision. Various obstacles and challenges have been identified, including the understanding of supervision itself by the principal, how to carry out academic supervision in the field, and how follow-up to supervision results can be carried out. The findings indicate that although academic supervision programs have a positive impact on improving teacher performance, further efforts are needed, starting from a correct understanding of the concept, planning and implementation of academic supervision itself to the follow-up provided so that academic supervision programs can provide great benefits for improving the quality of education as a whole.